Increasing of antioxidant and superoxide dismutase activity in chicory transgenic plants - Kvasko, O.Yu.; Matvieieva, N.A. (Вiopolymers and Cell, 2013)
Aim. Determination of the antioxidant activity (AOA) and superoxide dismutase (SOD) activity in transgenic chicory plants carrying the human interferon α2b target and nptII or bar selective genes. Methods. AOA was measured by a method based on the determination of kinetics of the reduced 2,6-dichlorophenolindophenol oxidation. SOD activity was assayed using the system consisting of ethionine, riboflavin, and nitroblue tetrazolium. Results. Antioxidant activity of transformed plants extracts was more than 1,91–2,59 and 2,04–2,43 times over the activity of control non-transgenic plants (at nptII and bar gene presence respectively). SOD activity was higher in transgenic plants than in the control, and was 2,03 ± 0,46–3,33 ± 0,54 U/g weight (nptII gene) and 2,25 ± 0,46–2,68 ± 0,08 U/g weight (bar gene). Conclusions. Transgenic C. intybus plants have higher antioxidant and superoxide dismutase activity compared to non-transgenic plants. The increasing of AOA and SOD activity is a response of plants to transformation stress factor and integration of foreign genes in plant genome. Мета. Визначення антиоксидантної активності (AOA) та активності супероксиддисмутази (СОД) у трансгенних рослинах цикорію з геном інтерферону-α2b людини та генами nptII і bar. Методи. АОА вимірювали методом, заснованим на визначенні кінетики окиснення відновленої форми 2,6-дихлорфенолін- дофеноляту натрію, активність СОД – за інтенсивністю інгібування тетразолю блакитного екстрактом рослин. Результати. АОА екстрактів трансформованих рослин перевищує активність контрольних (нетрансгенних) у 1,91–2,59 і 2,04–2,43 разу (гени nptII і bar відповідно). Активність СОД виявилася вищою у трансгенних рослин і становить 2,03 ± 0,46–3,33 ± 0,54 (ген nptII) і 2,25 ± 0,46–2,68 ± 0,08 (ген bar) ум. од/г сирої маси. Висновки. У трансгенних рослини C. intybus спостерігається підвищена активність антиоксидантної системи і СОД, що, вірогідно, є реакцією рослин на дію трансформації як стресового фактора. Стресовий стан трансгенних рослин цикорію може бути пов’язаний із перенесенням чужорідних генів до геному рослин. Цель. Определение антиоксидантной активности (AOA) и активности супероксиддисмутазы (СОД) в трансгенных растениях цикория с геном интерферона α2b человека и генами nptII и bar. Методы. АОА измеряли методом, основанным на определении кинетики окисления восстановленной формы 2,6-дихлорфенолиндофе- нолята натрия; активность СОД – по интенсивности ингибирования тетразолия голубого экстрактом растений. Результаты. АОА экстрактов трансформированных растений превышала активность контрольных (нетрансгенных) в 1,91–2,59 и 2,04–2,43 раза (гены nptII и bar соответственно). Активность СОД была выше у трансгенных растений и составляла 2,03 ± 0,46–3,33 ± ± 0,54 (ген nptII) и 2,25 ± 0,46–2,68 ± 0,08 (ген bar) усл. ед/г сырой массы. Выводы. Трансгенные растения C. intybus имеют повышенную активность антиоксидантной системы и СОД, что, вероятно, является реакцией растений на трансформацию как стрессовый фактор. Стрессовое состояние трансгенных растений цикория, очевидно, связано с перенесением чужеродных генов в геном растений.